Rumination in adolescents at risk for depression. - Kuyken, W; Watkins, E; Holden, E; Cook, W (2006)
BACKGROUND: Identifying high-risk adolescents and understanding first onset of depression in adolescence are important steps in reducing depression morbidity. There is compelling evidence that the personality dimension neuroticism is a risk factor for depression, but the vulnerability mechanism is not yet understood. This study examined the association between a hypothesized psychological vulnerability factor (rumination) and depression in adolescents. METHODS: A behavioural high-risk design differentiated a sample of 326 adolescents (aged 14-18) as either at normal or high risk for depression (operationalized as scores on a measure of neuroticism). RESULTS: Adolescents at risk for depression reported more rumination than adolescents not at risk. We hypothesized that the well established relationship between neuroticism and depression would be mediated by rumination in cross-sectional analyses, and our findings suggest that rumination partially mediated this relationship. CONCLUSIONS: The findings tentatively suggest that neuroticism acts as a risk factor for adolescent onset depression through increased tendency towards brooding rumination (i.e. moody self-evaluative dwelling) in response to depressed mood. Prospective and experimental research examining this mechanism is required.